Pilgrims and Puritans, 1620-1676 - Collier, Christopher, 1930-; Collier, James Lincoln, 1928- (New York : Benchmark Books, 1998)
Recounts the religious, political, and social history of the Massachusetts Bay Colony, and its influence on our lives today
Includes bibliographical references (p. 87-89) and index
Keywords: Pilgrims (New Plymouth Colony) -- Juvenile literature; Puritans -- Massachusetts -- History -- 17th century -- Juvenile literature; Pilgrims (New Plymouth Colony); Puritans; Massachusetts -- History -- New Plymouth, 1620-1691 -- Juvenile literature; Massachusetts -- History -- New Plymouth, 1620-1691